مسؤولية المصرف عن فحص المستندات في عملية الاعتماد المستندي وفقا للأصول والأعراف الموحدة للاعتمادات المستندية: نشرة رقم 600 - عريبي، مصطفى إبراهيم أحمد; معزب، عبدالخالق صالح عبدالله (الأكاديمية الأمريكية العربية للعلوم والتكنولوجيا, 2020)
يتناول هذا البحث فحص المستندات في الاعتماد المستندي، بالتركيز على دور المصرف في عملية الفحص والمسؤولية المترتبة من الناحية القانونية على نتائج الفحص. وقد تم اتباع المنهج الوصفي والتحليلي في البحث، من حيث تعريف الاعتماد المستندي والمستندات المطلوبة لفتح الاعتماد المستندي وأطرافه، ومعيار الفحص وما يترتب على الفحص، بموجب نصوص الأعراف والأصول الموحدة للاعتمادات المستندية نشرة (600)، واستعراض ما جاء في النشرات السابقة ومقارنتها بما هو نافذ. وقد تم تقسيم البحث إلى مبحثين وخاتمة، اشتمل كل مبحث على ثلاث مطالب تحدثنا في المبحث الأول عن الاعتماد المستندي من حيث (الأهمية- الوظيفة -التعريف- الأطراف- التكييف القانوني)، ويعرف على أنه عملية مصرفية ذات طبيعة قانونية خاصة. وهو عقد ثلاثي الأطراف، البنك والمشتري والبائع. تحدثنا في المبحث الثاني عن التزام المصرف بفحص المستندات، والتي تعتبر أساس عملية الاعتماد المستندي وتقسم إلى نوعين هما المستندات الأصلية والمستندات الثانوية، كما أوضحنا فيه طبيعة التزام المصرف بفحص المستندات، ومعايير الفحص والمعيار الذي تبنته القواعد والأعراف الموحدة، ومسؤولية المصرف عن المستندات المخالفة. وقد خلص البحث إلى عدد من النتائج والتوصيات من أهمها، أن فحص المستندات يكون من حيث الظاهر، ويجب على المصرف في حالة عدم مطابقة التقديم اتخاذ الإجراءات التي وردت في المادة (16) من القواعد والأعراف الموحدة.
This research discusses mainly examination of documents in documentary credit focusing on bank obligation to examine documents and its responsibility of such examination. Researchers followed descriptive and analytical method to explain definition of Documentary Credit, Presented Documents, parties of documentary credit contract, standard of examination and results of examination according ICC Uniform Customs and Practice for Documentary Credits (UCP 600) and compare them with ex provisions of ICC (UCPs). This research is divided into two chapters and conclusion; every chapter consists of three sections. We discussed in the first chapter of documentary credit in terms of (Importance, function, definition, and Legal Conditioning), It is defined as a bank operation of a particular legal nature and is a tripartite contract. Parties (bank, buyer, and seller). In the second chapter, we discussed the bank commitment to inspect the documents that are the basis of the accreditation process, and they are divided into two types, the original and secondary documents. We also explained, the nature of the bank’s commitment to examining documents and examination standards, what is the standard adopted by the unified rules and customs, and the bank’s responsibility for the documents in violation. The research concluded with a number of findings and recommendations, the most important of which is that the examination of documents is done on the surface. The bank, should non-conformity, shall carry out the procedures set forth in article (16) of the uniform rules.
Keywords: الاعتمادات المستندية -- المسؤولية المصرفية -- التنظيمات القانونية -- عقود البيع